Načrti in rezultati raziskovanja slovenskega izseljenstva do leta 1941 - s posebnim poudarkom na izseljevanju v Ameriko do prve svetovne vojne - Drnovšek, Marjan (Dve domovini, 1993)
The author outlines his thoughts on the plans and results of research on the emigration of Slovenes to America up until the First World War. He presents an overview of contemporary published and rare professional analyses on emigration until 1914, and includes journalistic and increasingly scientific analyses from the period 1919 to 1941.
Keywords: Slovenci; Slovenes; slovenski izseljenci; United States of America; ZDA; zgodovinski pregledi